The psychosocial and economic impacts on female caregivers and families caring for children with a disability in Belu District, Indonesia. - Gregorius Abanit Asa; Nelsensius Klau Fauk; Paul Russell Ward; Lillian Mwanri (PLoS ONE, 2020)
The current study aimed to understand psychosocial and economic impacts of female caregivers and families caring for children with a disability in Belu district, Indonesia. A qualitative inquiry employing one-on-one in-depth interviews was used to collect data from participants (n = 22). Data analysis was guided by a framework analysis for qualitative research. Social implications framework and the economic consequence of disease and injury framework were used to guide the conceptualisation, analysis and discussion of the findings. Findings indicated that female caregivers of children with a disability experienced significant psychosocial challenges. These included feeling frustrated, sad, angry, worried, inferior and insecure due to rejection of their children by other kids with no disability. Poor physical conditions of and negative labelling given to their children and the fear of what the future held for their children with a disability added yet another layer of psychosocial challenges experienced by these women. Separation or divorce and reduced social interaction and engagement in the community were expressed social impact loaded to these women resulting from poor acceptability of the children by their fathers, increased time spent caring and discriminatory and stigmatising attitudes against their children with a disability. The participants also experienced economic impacts, such as increased health and transport expenses, loss of jobs and productivity, and lack of savings. The findings indicate the need for programs and interventions addressing the needs of mothers or female caregivers and families with disabled children. Further studies with large number of participants covering mothers, fathers and caregivers to understand broader experiences and the need of caring for children with a disability are recommended.